Electrical conductivity of unidirectional carbon fiber composites with epoxy-graphene matrix. (September 2018) - Wentzel, Daniel; Sevostianov, Igor
Abstract: This paper aims at establishing connections between electrical resistivity and stresses in carbon fiber reinforced epoxy-graphene composites. To avoid the interconnection of multiple parameters, we examined composite specimens consisting of a single strand or tow (12, 000 carbon fiber filaments) embedded in an epoxy matrix containing up to 1.0 wt% of graphene (TG679) particles. The specimens show resistance increase with the tensile stress. The characteristic of the dependence varies with the content of graphene particles, tending to be linear as the percentage of graphene content increases. We did not observe any significant changes in the ultimate strength of the composite with an increase of the graphene particles concentration.